Research on the production of the kit for rapid detection of Vibrio cholerae in water - Quyen, Ha Thi; Quan, Duong Hong; Khang, Dinh Duy; Cam, Phuc Dac (Academia Journal of Biology, 2014)
Vibrio cholerae is a causative agent of the epidemic diarrheal. Vibrio cholerae is a noninvasive organism affecting the small intestine through the secretion of the enterotoxin. For rapid detection of Vibrio cholerae, we have developed the kit based on PCR amplification of the gene encoding enterotoxin (ctx) of this agent. The bacteria is captured from water by the bacterial filter with the aid of a pump and enriched in the specific medium for Vibrio cholerae. The genetic material are released from bacteria by heat treatment and the specific fragment is amplified by PCR. The kit has been tested with different enterobacteria such as Esherichia coli, Salmonella typhi, Shigella flexneri and the result showed that the test was sensitive and specific for the Vibrio cholerae detection.